Psychosocial Factors and Preterm Birth Among Black Mothers and Fathers. Issue 5 (September 2018) - Giurgescu, Carmen; Misra, Dawn P.
Abstract: Objective: Black women are more likely to live in disadvantaged neighborhoods and experience racial discrimination and psychological stress compared with White women. These factors have been related to preterm birth (PTB). However, research is limited on the associations of disadvantaged neighborhoods, racial discrimination, and psychological stress among expectant Black fathers and PTB. This review focuses on what is known about psychosocial factors in relation to PTB among Black parents. Methods: The Scopus database was used to search for studies using keywords of adverse childhood experiences, neighborhood environment, racial discrimination, psychological stress, depressive symptoms/depression, coping, locus of control, social support, and mother–father relationship. Each of these keywords was combined with the term preterm birth. This review focused on the associations of these psychosocial factors collected during the prenatal period and risk for PTB. However, due to lack of data for some of these factors during the prenatal period, studies conducted in the immediate period after birth were included. The focus of this review was on research conducted with Black expectant fathers given the limited data on the association between paternal psychosocial factors and PTB. This review only highlights studies that examined the associations of maternal psychosocial factors and PTB. It does not present a comprehensive review of studies on maternal factors given the extent of the studies that examined these associations. Results: Pregnant Black women are more likely to report living in disadvantaged neighborhoods; experiencing racial discrimination, psychological stress, and depressive symptoms; using avoidance coping; and reporting lower levels of social support compared with White women. Limited data suggest that Black expectant fathers experience higher rates of everyday unfair treatment because of race/ethnicity compared with White fathers. Research suggests that these psychosocial factors have been related to PTB among pregnant Black women; however, research is limited on examining these associations among expectant Black fathers. Clinical Implications: Maternal–child nurses are in the position to assess these psychosocial factors among expectant parents. Nurses should also assess risk factors for PTB for both expectant parents and provide support to couples who are at risk for PTB. Abstract : Black mother-Black father couples are two times more likely to have preterm birth compared to White mother-White father couples. In a review of the literature, potential factors for this disparity are explored. Gaps in evidence are highlighted. Suggestions for action based on what is known are offered.